2003
DOI: 10.2134/agronj2003.1591
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Spread of Kura Clover in Cool‐Season Grass Pastures

Abstract: promise for longevity in pastures of the north-central USA (Sheaffer et al., 1992). Exceptional winterhardi-Legumes can improve productivity and quality of cool-season grass ness, tolerance to drought (Black and Lucas, 2000; Watpastures but often do not persist under grazing. In May of 1997 and 1998, field experiments were planted in cool-season grass pastures son et al., 1998), and tolerance to frequent defoliation near Morris, MN, to evaluate establishment and persistence of kura (Peterson et al., 2002; Pete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Kura clover has the potential to cause bloat when contributing in large proportions to total forage yield (10,15). Kura clover has been reported to successfully establish with different grasses species, either when direct-seeded in mixtures or used to renovate grass-dominated pastures (1,5,6,16). Despite its great potential, KC use remains marginal mainly due to a characteristic slow development (3,5,6,13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kura clover has the potential to cause bloat when contributing in large proportions to total forage yield (10,15). Kura clover has been reported to successfully establish with different grasses species, either when direct-seeded in mixtures or used to renovate grass-dominated pastures (1,5,6,16). Despite its great potential, KC use remains marginal mainly due to a characteristic slow development (3,5,6,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its great potential, KC use remains marginal mainly due to a characteristic slow development (3,5,6,13,14). Kura clover's contribution to yield is initially minimal; it however gradually increases in post-seeding years (1,2,5,6). If KC's development pattern is well known, there is however limited information on how KC yield contribution over time may differ when seeded with various grass species.…”
Section: Introductionmentioning
confidence: 99%
“…It is debatable whether such a slow rate of improvement could be recommended for practical application, although slow colonization is not unique to the species or conditions studied here; Cuomo et al (2003), for example, reported that Kura clover took 4 years from planting to reach its greatest stand density. If vegetative spread provides a more persistent stand of legume, as indicated by Beuselinck et al, (1994) and Woods and Caddel (1994), then slow colonization may be acceptable in low-input systems, especially if it is associated with low cost and limited disturbance to existing pasture.…”
Section: Forage Nitrogen Concentration and Yieldmentioning
confidence: 96%
“…Overseeding with lespedeza increased harvested N yield by an average of 40 kg ha −1 over four years. The effect of cool-season overseeding on N yield was most apparent in the years (2002 and 2003) immediately following sowing of legumes and was reduced in the final two years of the experiment, so that there was no significant difference in N yield between legume-oversown and unimproved pasture plots by the final year of the experiment (Table 5. , based on Cuomo et al, (2003), can be established by no-till seeding into nearly-dormant unimproved warmseason pasture. The results showed, however, that establishment of an apparently satisfactory plant stand did not necessarily result in significant production of legume.…”
Section: Forage Nitrogen Concentration and Yieldmentioning
confidence: 99%
See 1 more Smart Citation